Overexcitability: Uniqueness Development of Gifted and Talented Muslim Students - Aisyah Nabihah Sofea Amran; Daniel Fandi Ngieng; Amnah Zanariah Abd Razak (Kolej Genius Insan, Universiti Sains Islam Malaysia, 2024)
2nd Insan Junior Researchers International Conference 2021 (iJURECON 2021) “STREAM for a Better Life” 15-17th October 2021 Organized By :Kolej GENIUS Insan of Universiti Sains Islam Malaysia